Answers

2015-05-14T23:00:56+05:30
-5/6 -1/3 ( lcm of 6, 3 is 6)    and                2/3-(6/-5)
= -5-1(2)/6                                             =  2/3+6/5  (lcm of 3, 5 is 15)
= -5-2/6                                                 =  2(5)+6(3)/15
= -7/6                                                    = 10+18/15
                                                            =  28/15

then,
[- 5/6 - 1/3 ] / [2/3 - 6/-5] = [-7/6] / [28/15]
                                    = -7/6 × 15/28
                                    = -1/2 × 5/4
                                    =  -5/8
                                    =  -0.625
therefore, 
[- 5/6 - 1/3 ] / [2/3 - 6/-5] = -0.625
1 5 1